Alice, darling [videorecording (DVD)] - Francis, Alanna; Pallett, Owen, 1979-; Scales, Gareth C.; Kendrick, Anna; Horn, Kaniehtiio; Carrick, Charlie; Mosaku, Wunmi (Lionsgate, 2023)
"In the taut thriller Alice, a woman, is pushed to the breaking point by her psychologically abusive boyfriend, Simon. While on vacation with two close girlfriends, Alice rediscovers the essence of herself and gains some much-needed perspective. Slowly, she starts to fray the cords of codependency that bind her. But Simon's vengeance is as inevitable as it is shattering and, once unleashed, it tests Alice's strength, her courage, and the bonds of her deep-rooted friendships."--Container.